Experimental investigation on two-phase flow noise characteristics of R410A through electronic expansion valve of multi-split air conditioner. (February 2023) - Zhou, Shaohua; Zhan, Feilong; Ding, Guoliang
Highlights: Gurgling noise and hissing noise are two kinds of flow noise in the EEV. Hissing noise is sharper and more severe than gurgling noise. Oscillation of bubbles with small size is prone to increase the noise frequency. Sound pressure level firstly increases and then decreases as quality increases. Liquid film of annular flow pattern has the function of weakening flow noise transmission. Abstract: The refrigerant flowing through an electronic expansion valve (EEV) of a multi-split air conditioner is usually in two-phase state which may generate more severe flow noise than that in sub-cooled state. The purpose of this paper is to experimentally investigate the influences of the two-phase R410A operation conditions on the flow noise characteristics in the EEV, including listening sense forms, frequency distributions and sound pressure levels (SPLs). The experimental conditions cover the refrigerant mass flow rate ranging from 30 to 90 kg h –1 and the refrigerant quality ranging from 0.02 to 0.4. The results show that low mass flow rate facilitates the reduction of noise frequency, and the peak noise frequency was reduced by up to 32% as the mass flow rate decreased. Low refrigerant quality helps to reduce the SPL of flow noise, and the average SPL decreased by 6 dB as the refrigerant quality decreased. The guidance of inlet flow pattern by transforming the churn flow to the annular flow helps to simultaneously reduce the noise frequency and SPL, and the peak noise frequency as well as the averaged SPL decreased by 47% and 4 dB, respectively. Moreover, the hissing noise and the gurgling noise are the only two kinds of listening sense forms of flow noise detected in the present experiment, and the peak frequency and the average SPL of hissing noise are both higher than those of gurgling noise.